Model Akuntabilitas Birokrasi di Era Otonomi Khusus Aceh: (Tinjauan terhadap Tes Shalat dan Baca Al-Qur’an di Kabupaten Aceh Barat Daya) - Ferizaldi (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2018)
The implementation of local government in the context of the Special Autonomy of Aceh has the freedom of the regional government to administer government in accordance with the principles of good governance. In Indonesia it is regulated by Law No. 28 of 1999 concerning the Organization of a clean and free country of corruption and nepotism, through various innovations and creativity to create good governance based on the public interest. This is to answer various problems surrounding the low performance of the bureaucracy because many are entangled in various corruption cases. One attempt to change the government bureaucracy is good, then introduced a new model through local wisdom in the Southwest Aceh District of Aceh Province, by carrying out the Prayer Test and Reading the Qur’an to prospective structural officials, as an effort to reform bureaucracy to create bureaucratic accountability, which It is expected that these activities will produce bureaucrats who are religiously accountable and customer oriented. However, this program must be carried out in a sustainable and comprehensive manner through complementary programs that support the program and do not underestimate the supervision efforts which as a classic action create a healthy bureaucracy.